2021
DOI: 10.3390/su13063288
|View full text |Cite
|
Sign up to set email alerts
|

Food Waste in Healthcare, Business and Hospitality Catering: Composition, Environmental Impacts and Reduction Potential on Company and National Levels

Abstract: Background: As the reduction of food wastage remains one of our most critical challenges, we quantified the environmental impacts of food losses in the food-service sector in Germany, with a particular focus on the subsectors of business, healthcare and hospitality. Methods: Using the food-waste data of 7 catering companies, 1545 measurement days and 489,185 served meals during two 4–6 week monitoring periods, a life-cycle assessment (LCA) according to ISO standard 14040/44 was conducted. Within the LCA, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Appropriately applying the consensus pathway food waste audit tool may then promote possible outcomes such as decreases in waste, monetary savings and workflow enhancements. Moreover, if the use of the consensus tool is magnified to other food providing institutions experiencing high amounts of food waste such as aged care, prisons and childcare ( 37 ), this could have large influences on the economic, social and environmental impacts associated with food waste ( 38 ). This may promote reputational sustainability within these organisations or industries and ( 39 ) will contribute to the actions required to meet UN SDG 12.3 ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriately applying the consensus pathway food waste audit tool may then promote possible outcomes such as decreases in waste, monetary savings and workflow enhancements. Moreover, if the use of the consensus tool is magnified to other food providing institutions experiencing high amounts of food waste such as aged care, prisons and childcare ( 37 ), this could have large influences on the economic, social and environmental impacts associated with food waste ( 38 ). This may promote reputational sustainability within these organisations or industries and ( 39 ) will contribute to the actions required to meet UN SDG 12.3 ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation and feedback systems for assessing the quality, taste, hygiene, nutrition, and other information related to the restaurant's meals should be improved to enhance perceived behavioral control among consumers. In addition, education on sustainable food consumption and shopping planning strategies and knowledge about the resource and environmental impacts of food production should be strengthened to provide consumers a stronger perception of reducing food waste [5] and its related issues such as carbon emissions and the inefficient use of land, water, and labor [39,89,90]. This information will help promote moral responsibility among consumers, and thus change their attitudes and behaviors to reduce waste.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…6 Another recent study has compared the emissions associated with food waste produced in healthcare with other foodservice sectors, finding greenhouse gas emissions, land use, and eco-points were highest for hospitality followed by healthcare and then business. 7 Measuring waste is important to provide a baseline to understand the current situation, model the impact of different waste reduction strategies, and monitor progress. Attempts to measure food waste have been the focus of recent government policy directives at the national, state and local levels in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Thiel et al reported that the annual carbon emissions associated with food and packaging waste from foodservices in one New York hospital (294 466 kg CO 2 e per year) was equivalent to the emissions produced by 64 standard US passenger cars 6 . Another recent study has compared the emissions associated with food waste produced in healthcare with other foodservice sectors, finding greenhouse gas emissions, land use, and eco‐points were highest for hospitality followed by healthcare and then business 7 …”
Section: Introductionmentioning
confidence: 99%